Field testing of VO2 peak in cross-country skiers with portable breath-by-breath system - Doyon, K. H.; Perrey, St.; Abe, D.; Hughson, R. L. (Canadian Journal of Applied Physiology, 2001)
Peak aerobic exercise responses were determined in 8 competitive cross-country skiers during field-testing and during an incremental treadmill test (TM) to determine peak oxygen uptake (VáO2peak), heart rate, and oxygen pulse. Field testing consisted of maximal effort roller skiing using diagonal stride (DS) and double poling (DP) techniques. VáO2 was measured during roller skiing by the portable Cosmed K4b2 breath-by-breath system. The portable system was compared against a standard laboratory mixing box system, and no differences were found across the full range of VáO2. During DS, VáO2peak and oxygen pulse were not different from TM, whereas peak HR was lower. With DP, VáO2peak and oxygen pulse were less than DS or TM, whereas peak HR was less than with TM but not different from DS. These results demonstrate the validity and utility of the portable breath-by-breath system for measurement of aerobic energy demand of athletes as they carry out their normal activity.